2016
DOI: 10.1016/j.exger.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between mitochondrial function and walking performance in older adults with a wide range of physical function

Abstract: Background Age related declines in walking performance may be partly attributable to skeletal muscle mitochondrial dysfunction as mitochondria produce over 90% of ATP needed for movement and the capacity for oxidative phosphorylation decreases with age. Methods Participants were from two studies: an ancillary to the Lifestyle Interventions and Independence for Elders (LIFE) Study (n = 33), which recruited lower functioning participants (Short Physical Performance Battery [SPPB], 7.8 ± 1.2), and the Study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…However, this association was no longer statistically significant when the analysis was adjusted for age and BMI (β = −.025, p = .848 and β = .184, p = .192, respectively). P 31 MRI spectroscopy studies have reported a significant correlation between mitochondrial function and muscle strength, suggesting that muscle function mediates the association between mitochondrial function and mobility (Choi et al., ; Santanasto et al., ; Zane et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this association was no longer statistically significant when the analysis was adjusted for age and BMI (β = −.025, p = .848 and β = .184, p = .192, respectively). P 31 MRI spectroscopy studies have reported a significant correlation between mitochondrial function and muscle strength, suggesting that muscle function mediates the association between mitochondrial function and mobility (Choi et al., ; Santanasto et al., ; Zane et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Again, our findings could be due to the heterogeneity of the effect in the analyzed samples. For example, it has been shown that the mitochondrial function is associated with walking performance in higher functioning active older adults, but not lower functioning sedentary adults (Santanasto et al., ). Interestingly, we found a significant negative correlation of respiration in State 4, Submaximal State 3, and State 3 with the 400‐m walk test, a proxy of mobility and fatigability.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, participants were carefully matched for physical activity using both accelerometry (Table 1) and questionnaires. Prior studies have associated a decline in mitochondrial function with walking performance in older adults (Coen et al, 2013;Santanasto et al, 2016) and in patients with PAD (Hou et al, 2002), while also demonstrating the beneficial effects of exercise to off-set this age-related decline in mitochondrial function (Joseph, Adhihetty, & Leeuwenburgh, 2015). Furthermore, the efficacy of physical activity to preserve mitochondrial function with age would most likely translate into preserved mitochondrial function with maintained physical activity in patients with PAD.…”
Section: Mitochondrial Respiratory Function In Patients With Padmentioning
confidence: 98%
“…176 ATPmax and mitochondrial respiration rates measured in permeabilized muscle fibers also correlate with walking speed in older adults. 177,178 Walking speed and function is a particularly relevant readout as this is directly related to functional independence in the elderly.…”
Section: Dysregulation Of Mitochondrial Energetics During Disuse Atrophymentioning
confidence: 99%